Natural and synthetic flavonoid modulation of TRPC5 channels. (13th January 2016) - Naylor, Jacqueline; Minard, Aisling; Gaunt, Hannah J; Amer, Mohamed S; Wilson, Lesley A; Migliore, Marco; Cheung, Sin Y; Rubaiy, Hussein N; Blythe, Nicola M; Musialowski, Katie E; Ludlow, Melanie J; Evans, William D; et al.
Abstract : Background and Purpose: The TRPC5 proteins assemble to create calcium‐permeable, non‐selective, cationic channels. We sought novel modulators of these channels through studies of natural products. Experimental Approach: Intracellular calcium measurements and patch clamp recordings were made from cell lines. Compounds were generated by synthetic chemistry. Key Results: Through a screen of natural products used in traditional Chinese medicines, the flavonol galangin was identified as an inhibitor of lanthanide‐evoked calcium entry in TRPC5 overexpressing HEK 293 cells (IC50 0.45 μM). Galangin also inhibited lanthanide‐evoked TRPC5‐mediated current in whole‐cell and outside‐out patch recordings. In differentiated 3T3‐L1 cells, it inhibited constitutive and lanthanide‐evoked calcium entry through endogenous TRPC5‐containing channels. The related natural flavonols, kaempferol and quercetin were less potent inhibitors of TRPC5. Myricetin and luteolin lacked effect, and apigenin was a stimulator. Based on structure–activity relationship studies with natural and synthetic flavonols, we designed 3, 5, 7‐trihydroxy‐2‐(2‐bromophenyl)‐4 H ‐chromen‐4‐one (AM12), which inhibited lanthanide‐evoked TRPC5 activity with an IC50 of 0.28 μM. AM12 also inhibited TRPC5 activity evoked by the agonist (−)‐Englerin A and was effective in excised outside‐out membrane patches, suggesting a relatively direct effect. It inhibited TRPC4 channels similarly, but its inhibitory effect on TRPC1–TRPC5 heteromeric channels was weaker. Conclusions and Implications: The data suggest that galangin (a natural product from the ginger family) is a TRPC5 inhibitor and that other natural and synthetic flavonoids contain antagonist or agonist capabilities at TRPC5 and closely related channels depending on the substitution patterns of both the chromone core and the phenyl ring.